Robust Stormwater Strategies under Climate Change: A Case Study in Somerville, Massachusetts. - Caputo, Lauren. (2017)
Abstract: Stormwater management systems involve many challenges including flooding and associated property damage, combined sewer overflows, and poor water quality in surface waters. All these may be exacerbated under a changing climate in the future. This study uses a detailed methodology to identify robust adaptation strategies for managing urban stormwater under climate change uncertainty. Robust strategies are strategies that function acceptably well under all future uncertainties and risks. The objective of this study is to investigate effective responses for urban water managers to the challenges of drainage management in conditions of a changing climate through a new methodology. Robust adaptation strategies are evaluated for a combined sewer system in Somerville, Massachusetts using the U.S. EPA Storm Water Management Model (SWMM). Various design storms are simulated in 2010, 2040, and 2070 under low, moderate, and high climate change scenarios. Five strategies for stormwater/CSO management are tested under these conditions to find a strategy which performs well under all conditions considered, which we term a robust strategy. Two decision-making approaches are used to quantify results: a design cost approach and a net benefits approach. Both approaches utilize risk analysis for each climate change scenario to determine the expected values of costs, and in the case of net benefits, the benefits of management. Costs to meet design criteria are compared for each climate change scenario to identify the most cost-effective robust strategy. Similarly, net benefits are compared and the most beneficial robust strategy is identified. This methodology identifies sewer separation as the best robust strategy under both approaches.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Civil Engineering.; Advisors: Richard Vogel, and Paul Kirshen.; Committee: Paul Mathisen.; Keyword: Environmental engineering.